Strategie wejścia na rynek hotelarski - Szymfel, Marcin (Entering Strategies for Hotel Industry, 2008)
The paper describes the process of entering hotel market with the use of different business approaches. One of the key aspects which must be considered prior to investment decision is both: location of the building as well as the pricing model used in the investment. Hotels use two typical pricing models, non-elastic which supports production from contracted segments and elastic which supports production from non-contracted segments. Whilst it is said that non-elastic model will support hotel objectives by delivering stable number of room nights during the entire investment period it has been proved that non-elastic delivery generates inferior business results to elastic model. The research conducted amongst six 5 star hotels in Warsaw covering years 2003-2007 has proved that the hotel with fully flexible pricing model is able to deliver superior results both in high as well as in low season.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 376-385